PREPARATION OF ELECTROCHEMICALLY IMMOBILIZED IRON ON THIN FILM FAUJASITE-NANOZEOLITE MODIFIED GLASSY CARBON - Yuni K. Krisnandi; Ivandini T. Anggraningrum; Hanny Tovina; Aminah Aminah (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2011)
PREPARATION OF ELECTROCHEMICALLY IMMOBILIZED IRON ON THIN FILM FAUJASITE-NANOZEOLITE MODIFIED GLASSY CARBON. Metal iron that electrochemically immobilized on thin film faujasite type of nanozeolite (FAU-nanozeolite) grown on polyelectrolyte (PDDA, PSS, PDDA layers) modified glassy carbon has been prepared. Thin film of FAU-type nanozeolite was synthesized using seeding method. The seeded modified-glassy carbon then was immersed in FAU colloidal suspension at 100 oC for certain period. XRD patterns of the seed and as-synthesized zeolite powder have similarity with the patterns from standard NaY zeolite. SEM images of thin film nanozeolite also show the appearance of crystals with homogeneous size of about < 1 μm. The best spread thin film was obtained when using 3 ml seed and immersion in colloidal FAU solution for 20 hours. The thin film then was utilized for metal iron synthesis, in which Fe(III) from FeNO3 solution containing Na-citrate of that adsorbed on the surface of thin film was electrochemically reduced to (Fe0). SEM image shows some aggregates (size > 100 nm) of the nanozeolite thin film. However, it can also be seen that the crystals actually consist of smaller particles with size < 100 nm. The EDS mapping of the surface indicates that after electrochemical treatment, the surface of thin film consists of about 0.30% (w/w) iron that spread evently both on the surface covered by nanozeolite thin film and that from modified glassy carbon.